Transforming Education: Comparative Analysis of Socio-Economic Policies from Malaysia to Thailand - Chaiya, Chitralada (Journal of Ecohumanism, 2024)
This study critically examines how strategic socio-economic policies act as catalysts for educational transformation, focusing on Malaysia and Thailand within the ASEAN region. By analyzing GDP allocations to education and their influence on QS World University Rankings from 2012 to 2022, the research reveals a positive correlation between increased educational investment and improvements in university rankings. However, it also identifies significant inefficiencies in fund utilization, highlighting that merely increasing funding does not guarantee improved educational outcomes. The findings expose gaps in policy implementation and emphasize the need for more strategic, outcome-oriented deployment of educational resources. Integrating management theories with empirical evidence, this study contributes to the discourse on effective resource management in education. It offers valuable insights for policymakers and educational administrators on aligning socio-economic strategies with educational practices. The research advocates for a comprehensive understanding of the relationship between financial investments and educational quality, emphasizing the necessity for reforms that enhance the efficiency and impact of educational funding. These reforms are crucial for improving the international standing of higher education institutions and fostering broader socio-economic development.